Association of ceramide risk scores with rheumatoid arthritis: a FINRISK population-based cohort study - Jaakko Tuomilehto; Mitja Lääperi; Juha Sinisalo; Reijo Laaksonen; Mohammadreza Shoghli; A. Inkeri Lokki; Marja-Liisa Lokki; Mika Hilvo; Antti Jylhä (BMJ Open)
Objectives This study aimed to explore the association between lipid-based Cardiovascular Event Risk Tests (CERT1 and CERT2), including ceramides (Cer) and phosphatidylcholine (PC) lipid species, and rheumatoid arthritis (RA), an inflammatory disease that can increase the risk of cardiovascular diseases.Design Prospective population-based cohort study.Setting Primary care centres across five geographical areas in Finland.Methods The study included 7702 individuals (selected from the FINRISK cohort) who were assessed for the prevalence and incidence of RA. At baseline, the cohort included 7518 RA-free individuals, among whom 329 developed RA during the study, and 184 had a history of RA at baseline. Serum levels of ceramides and PC were measured using mass spectrometry, and CERT scores were calculated.Main outcome measures Prevalence and incidence of RA, CERT scores, and serum lipid levels.Results CERT scores were associated with prevalent RA but not with incident RA in the full cohort. Adjusted ORs and 95% CI for prevalent RA were 1.24 (95% CI 1.05 to 1.46) for CERT1 and 1.42 (95% CI 1.20 to 1.68) for CERT2. Stratified analyses showed that these associations were consistent among individuals over 50 years of age and across both sexes. The Cer (d18:1/16:0)/PC (16:0/22:5) ratio was significantly associated with RA in younger individuals (OR 1.66; 95% CI (1.26 to 2.18)). Overall, the association between lipids and RA was stronger in women than men.Conclusions The study shows a significant association between prevalent RA and bioactive lipid species used for cardiovascular risk assessment. These findings emphasise the importance of considering residual inflammatory risks, such as RA, in cardiovascular risk evaluations in clinical settings.